Effect of high hydrostatic pressure on chlorophyll/soybean protein isolate interaction and the mixtures properties. (July 2022) - Cao, Jiarui; Li, Yuanyuan; Li, Fangwei; Liao, Xiaojun; Hu, Xiaosong; Zhang, Yan
Abstract: Chlorophyll (Chl) is highly susceptible to degradation due to food processing (especially thermal processing), resulting in color changes in food. This study was designed to examine the interaction between Chl and soybean protein isolate (SPI) after high hydrostatic pressure (HHP) treatment from fluorescence spectroscopy, SPI structure changes, and physical stability of mixtures as well as thermal stability perspectives. Based on fluorescence quenching analysis, binding constants ( K a ) and number of binding sites ( n ) were calculated. At 100 MPa, the K a (13.7670 × 10 5  L/mol) of SPI was the largest, forming a strong interaction, but the results at 300 MPa were completely different. The surface hydrophobicity (H0 ) of SPI significantly decreased due to the incorporation of Chl at 100 MPa, changing the tertiary and quaternary structures of SPI. Molecular docking showed that phytyls of Chl penetrated into the hydrophobic area of SPI and interacted with it, and porphyrin rings were mainly bound to regions with strong polarity in SPI. The particle size and polydispersity index (PDI) of mixtures were the smallest at 100 MPa, presenting a more compact and stable structure. The samples after HHP treatment were then treated at 80 °C. Chl showed a good color stability (higher retention and - a * values) at 100 MPa and 200 MPa with smaller changes in particle size and PDI value after thermal treatment. Altogether, the Chl-SPI interaction at high pressures appeared to have a positive effect on the stability of Chl and Chl-SPI mixtures. Graphical abstract: Image 1 Highlights: HHP treatment of 100 MPa can improve a stronger interaction between Chl and SPI. HHP altered SPI structure, promoting interactions of phytol and porphyrin rings with SPI, respectively. HHP treatment of 100 and 200 MPa contributed to the mixtures showing good color and physical stability.